Undrained Shear Strength of Unsaturated Soils under Zero or Low Confining Pressures in the Vadose Zone - Oh, T.W. (2020)
In geotechnical engineering practice, many projects such as stability analysis of slopes or trenches and pavement design involve soils in vadose zones at shallow depths, where soils are under unsaturated conditions. For these types of projects, undrained shear strength test results obtained under zero or low confining pressure can be effectively used to analyze the behaviors of unsaturated soils. Experimental procedures to determine the undrained shear strength for different soil suction values, however, is time consuming even under low confining pressure. For this reason, we attempted to develop a semi‐empirical model to predict the undrained shear strength of unsaturated soils at a shallow depth assuming zero confining pressure as a function of soil suction. In addition, existing empirical or semi‐empirical models are also presented along with the characteristic behaviors of unsaturated soils under axial forces at low or zero confining pressures. Finally, the advantages and disadvantages of each model are discussed based on the comparison between the measured undrained shear strengths under zero or low confining pressures with those predicted using the existing and proposed models.